Fire Science and Technology 2015 The Proceedings of 10th Asia-Oceania Symposium on Fire Science and Technology - Harada, Kazunori; Matsuyama, Ken.; Himoto, Keisuke; Nakamura, Yuji.; Wakatsuki, Kaoru; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book focuses on topics in the entire spectrum of fire safety science, targeting research in fires, explosions, combustion science, heat transfer, fluid dynamics, risk analysis, structural engineering, and other subjects. The book contributes to a gain in advanced scientific knowledge and presents or advances new ideas in all topics in fire safety science. Two decades ago, the 1st Asia-Oceania Symposium on Fire Science and Technology was held in Hefei, China. Since then, the Asia-Oceania Symposia have grown in size and quality. This book, reflecting that growth, helps readers to understand fire safety technology, design, and methodology in diverse areas including historical buildings, photovoltaic panels, batteries, and electric vehicles.
Keywords: Security systems; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Building materials; Renewable energy sources; Security Science and Technology; Engineering Thermodynamics, Heat and Mass Transfer; Building Materials; Renewable Energy